Fatal Hieroglyph: Mexico for Writers of Exile Malcolm Lowry and William Burroughs - DeGuzmán, María (Scripta, 2017)
This essay explores the representation of Mexico in the work of British modernist writer of exile Malcolm Lowry and of U.S. Anglo-American post-war, postmodern writer of exile William Burroughs. Lowry’s Under the Volcano (1947) and Burroughs’s trilogy The Soft Machine (1961), The Ticket that Exploded (1962), and The Nova Express (1964) represent Mexico as a land of fatal hieroglyphs, as itself a fatal hieroglyph. Theoretically, a hieroglyph, as a condensation of space and time, is always already fatal — “an anticipation of the end in the beginning” [Jean Baudrillard]. The fatal sign constitutes an attempted exorcism of conventional reality governed by the status quo. For Lowry and Burroughs, Mexico as place and text is the locus of the exorcism of demons, personal and cultural. In turning Mexico into a fatal hieroglyph of doom, both modernist and postmodernist writers draw on a long tradition of stereotyping primitivizations of Mexico. However, in the cases of Lowry and Burroughs, these stereotypical primitivizations also function as alternative modes of knowledge, symbol-making, and anti-narration, deliberate plumbings of the non-linear, irrational, and trans-temporal to deliver a backhanded blow against the European and Gringo colonizer / conqueror in Lowry’s case and the malaise of Anglo-American military-industrial capitalism in Burroughs’s.